Quantitative intermolecular interactions (Cl⋯Cl, Cl⋯F, and F⋯F) analysis of halogen substituted nicotinonitrile derivatives and in-silico anti-diabetic activity - Jaiswal A.; Mishra M.; Mitra M.D.; Ganji M.D.; Kumar V.; Tewari A.K.; Kumar R. (My University, 2025)
Here, we have synthesized the nicotinonitrile derivatives (1–4) for studies of intermolecular non covalent halogen-halogen interactions such as Cl⋯Cl, Cl⋯F, and F⋯F. The X-ray crystallography studies have revealed that compounds 1–3 have shown Cl⋯F interaction. In contrast,e compound 2 has shown Cl⋯Cl interaction, and compound 4 has shown F⋯F interaction. Further, these intermolecular interactions have also been quantified by Hirshfeld surface analysis. Furthermore, we have also done in-silico anti-diabetic activity with PDB id 2OLE compared with ertugliflozin and sitagliptin (DPP-4) inhibitors, which are used to treat type II diabetes mellitus. © 2024 Elsevier B.V.